The concept of mindfulness in information systems research: a multi-dimensional analysis. Issue 2 (1st March 2017) - Dernbecher, Sabine; Beck, Roman
Abstract: The concept of mindfulness has garnered increasing attention during the last decade. Initially proposed within the scope of information systems (IS) research as a means of creating a deeper knowledge foundation for decision making regarding information technology (IT) innovations, it soon became broadly applied throughout IS research. To gain a better understanding of the evolved diversity of this concept, this paper reviews and analyzes extant IS research by means of (a) the investigated IS themes, (b) the purpose of using the concept, (c) the level of application of the concept, and (d) the tendency to focus either on mindfulness, mindlessness, or both. By synthesizing research findings, we derive a high-level IS mindfulness theory. We then propose future research opportunities, such as the explanation of the relationships between different levels of mindfulness, applying mindfulness to bridge the different phases of the software development process, and the identification of guidelines for designing information systems that facilitate mindfulness. As the first review on the application of mindfulness in IS research, we contribute to the overall understanding of mindfulness and address the four abovementioned dimensions from which mindfulness emerges in order to demonstrate that mindfulness provides a meaningful platform for generating knowledge.